Molecular investigation of the intra-specific genetic variation in Plantago ovata Forssk. (Plantaginaceae): An insight into potential ancestral area distribution and probable time of dispersal versus vicariance events - Mohsenzadeh, Saeed; Sheidai, Masoud; Koohdar, Fahimeh (Phytotaxa, 2022)
Plantago ovata (Plantaginaceae) is a medicinal plant cultivated extensively in Western Asia for seed husk known as blonde Psyllium or Isabgol. Taxonomy of P. ovata is controversial at both species level and variety recognition for both the Old and New World. There has been no infra-specific rank recognition for P. ovata in Iran. Therefore, we attempted to recognize the variety of P. ovata of Iran for the first time by using both morphological and molecular data. We used internal transcribed spacerregion (ITS) to estimate the level of genetic variability in P. ovata and also suggest the potential ancestral area of distribution and provide the probable time for P. ovata dispersal. We identified P. ovata variety decumbens as the P. ovata plant growing in Iran. Data obtained separated Asian Plantago plant samples from African and North American plants, due to sequence divergence. We obtained the time of the divergence for these two groups to be around 5 M years ago and RASP analysis revealed that Iran is the probable ancestral area for the occurrence of Asian Plantago.